Do outreach activities in secondary STEM education motivate students and improve their attitudes towards STEM?. Issue 11 (24th July 2018) - Vennix, Johanna; den Brok, Perry; Taconis, Ruurd
ABSTRACT: The present study investigated outreach activities, developed by STEM-based companies or universities in co-creation with secondary education with the aim to inform students about and motivate them for a career in STEM by connecting the work-context with school-science. Although many of such activities are being offered, little is known about their effects. We investigated students' perceptions with the outreach learning environment, perceived need-fulfilment, self-reported motivation and attitudes towards STEM. Data were gathered from 729 high-school students engaged in 12 activities in the USA and the Netherlands. The students completed a questionnaire, which contained questions about four elements of our theoretical frame based on the Self-Determination-Theory (SDT). Perceived needs-fulfilment and motivation were measured using the basic-psychological-needs-scale and the self-regulation-questionnaire. Attitudes were measured using the test-of-science-related-attitudes. Learning environment perceptions were measured in a previous study using subscales of what-is-happing-in-this-classroom (WIHIC), constructivist-learning-environments-scale (CLES) and classroom-environment-scale (CES) and typified by activity characteristics. Multilevel analyses of variance were conducted for the two motivation scales (controlled and autonomous-motivation) and the two attitude scales (social-implication and career-interest). Activity characteristics explained almost all variance in these variables between activities. Specific characteristics of outreach activities that statistically significantly related to autonomous motivation and positive general attitudes towards STEM were: workshop-format, understanding science, an out-of-school component. The attitude towards a possible STEM-career was positively associated with autonomous-motivation and negatively associated with controlled-motivation. Thus, outreach learning environments indeed created opportunities to increase students' motivation in STEM and attitude towards STEM, but the impact varied according to particular characteristics of the activities.